Moving the Needle on Literacy: Lessons Learned from a School Where Literacy Rates Have Improved Over Time - Georgiou, George K.; Kushnir, Greg; Parrila, Rauno (Alberta Journal of Educational Research, 2020)
Literacy is the most important skill children are required to master during their early school life. At the same time, much has been written about both the inadequate preparation of teachers to teach reading and the ever-increasing number of poor readers in our schools. In this study, we examined teachers’ perceptions of the factors that have contributed to their school’s success in improving children’s literacy scores. We used a sequential explanatory mixed methods research design where Phase 1 involved collecting quantitative data to document the improvement in reading and asking the teachers to fill out a questionnaire, while Phase 2 comprised gathering qualitative data where the principal and a language arts teacher commented on the findings from Phase 1. The results revealed three important themes that teachers perceive contributing to their school’s success. First, teachers collaborate weekly on their own learning, plan instruction together, and provide support for each other. Second, formative assessments are shared within each grade and data are used to inform areas of growth, not to evaluate teachers’ performance. Third, the school focuses on improving reading and believes in the child’s continuous growth. Taken together, the findings of our study suggest that teachers perceive success to be a team effort grounded on theory and the principles of collaborative learning. Keywords: children, literacy, mixed methods, reading, professional development. La littératie constitue l’habileté la plus importante que les enfants doivent maitriser pendant leurs premières années à l’école. Parallèlement, on a beaucoup écrit sur la préparation inadéquate des enseignants en matière d’enseignement de la lecture et sur le nombre croissant d’élèves avec des compétences insuffisantes en lecture. Dans cette étude, nous avons examiné les perceptions qu’ont les enseignants des facteurs ayant contribué à la réussite de leur école dans l’amélioration des compétences des élèves en lecture. Nous avons employé un modèle exploratoire et séquentiel de recherche à méthodes mixtes. Pendant la première phase, nous avons recueilli des données quantitatives afin de documenter l’amélioration en lecture et avons demandé aux enseignants de compléter un questionnaire. La deuxième phase a consisté en la cueillette de données qualitatives ou le directeur de l’école et l’enseignant de langue ont commenté les résultats de la première phase. Les résultats ont révélé trois thèmes importants relatifs aux perceptions des enseignants quant à la réussite de leur école. En premier lieu, les enseignants collaborent de façon hebdomadaire sur leur propre développement, planifient les cours ensemble et s’appuient mutuellement. Deuxièmement, on partage les évaluations formatives entre enseignants de la même année et on étudie les données pour identifier les aspects à améliorer, pas pour évaluer la performance des enseignants. Troisièmement, l’école mise sur l’amélioration de la lecture et croit en l’épanouissement continu des élèves. Globalement, les résultats de notre étude indiquent que les enseignants perçoivent la réussite comme découlant d’un effort collectif ancré dans la théorie et les principes de l’apprentissage collaboratif. Mots clés : enfants, littératie, méthodes mixtes, lecture, développement professionnel